Menumbuhkan Minat Belajar Mengurangi Prokrastinasi: Tantangan Siswa Kelas X di SMA X - Dewa Ayu Intan Sukmayanthi; Nyoman Trisna Aryanata; Aritya Widianti (CV. Doki Course and Training, 2024)
The success of learning is influenced by students' interest in learning. When someone has an interest in learning, they will show a high level of interest and gladly pay attention to learning activities. However, a common phenomenon among students today is that teenagers spend more time on entertainment than completing academic tasks. This study aims to determine the relationship between learning interest and academic procrastination among 10th-grade students at SMA X. This study uses a quantitative research method with simple linear regression analysis. The subjects of this study were 241 10th-grade students at SMA X. The instruments used were a learning interest questionnaire from Prihatin (2017) with a reliability of 0.713 and a validity score of 0.654-0.706, and an academic procrastination questionnaire from Zakiah (2021) with a reliability of 0.923 and a validity score of 0.218-0.672. The results of this study show a significance of 0.000 (ɑ < 0.05) with a regression coefficient value of -0.912 and an R Square of 5.4%. This indicates a significant negative relationship between the variables, meaning that the higher the learning interest, the lower the academic procrastination, and vice versa. However, the researcher found that even with a high interest in learning, students may still experience moderate academic procrastination, which is influenced by their inability to prioritize tasks. There is a relationship between the factors of learning interest and academic procrastination among 10th-grade students at SMA X, amounting to 5.4%, with the remaining percentage influenced by other factors. Future researchers are encouraged to further develop this study by investigating other factors that were not examined in this research.